Human T-lymphotropic virus 1/2 infection among immigrants and refugees in Central Brazil, an emerging vulnerable population - Marinho, Thaís Augusto; Magalhães, Larissa Silva; dos Santos, Kamila Cardoso; Martins, Thaynara Lorrane Silva; Silva, Grazielle Rosa da Costa e; Silva, Ágabo Macedo da Costa e; Carneiro, Megmar Aparecida dos Santos; Caetano, Karlla Antonieta Amorim; Teles, Sheila Araújo; Martins, Regina Maria Bringel (Frontiers in Public Health, 2023)
Introduction Migratory flows play a significant role in the spread of human T-lymphotropic virus 1/2 (HTLV-1/2). In the last decade, a substantial migration of individuals occurred from Haiti and Venezuela to Brazil. However, data on the prevalence of HTLV-1/2 infection among these international migrants in Brazil are scarce. This study describes the prevalence of this infection among immigrants and refugees in Central Brazil. Methods A cross-sectional study was conducted with 537 international migrants in the State of Goiás, Central Brazil. Participants were interviewed, and blood samples were collected. Serological screening for anti-HTLV-1/2 was performed using an enzyme-linked immunosorbent assay (ELISA; Murex HTLV-I + II, DiaSorin, Dartford, UK), and seropositive samples were submitted for confirmation by a line immunoassay (INNO-LIA HTLV I/II, Fujirebio, Europe N.V., Belgium). Results The majority of participants were males (54.4%), between 18 and 50 years old (78%; mean age: 29.1 years), self-declared black (55.1%), reported 1 to 12 years of formal education (70.9%), and were either Venezuelans (47.9%) or Haitians (39.7%). Additionally, 50.1% were immigrants, 49% were refugees, and five were Brazilian children (0.9%) born to Haitian immigrant parents. The overall prevalence of anti-HTLV-1/2 was 0.95% (95% CI: 0.31–2.28), with HTLV-1 at 0.19% and HTLV-2 at 0.76%. All seropositive individuals (n = 5) were refugees from Venezuela, resulting in a rate of 2.26% for anti-HTLV-1/2, HTLV-1 (0.45%) and HTLV-2 (1.81%) among Venezuelan refugees. Of the demographic and behavioral characteristics evaluated, unprotected sexual intercourse and having more than one sexual partner (≥2) in the previous 12 months were associated with HTLV-1/2 seropositivity among Venezuelans. Conclusion This study revealed, despite the low seroprevalence of HTLV-1/2 among international migrants in Central Brazil, evidence of HTLV-1 and HTLV-2 infections in Venezuelan refugees. In addition, their characteristics highlight that specific social and health programs should be implemented for these emergent and socially vulnerable migrant groups.